ANALYSIS OF SHARIA BANK CHALLENGES IN OVERCOMING FINANCIAL RISK DURING THE COVID-19 PANDEMIC - Tri Auri Yanti; Sugianto Sugianto (Proceeding International Seminar of Islamic Studies, 2022)
The background of this research is based on the phenomenon of financial risk that occurred during the Covid-19 pandemic. This research is a descriptive and empirical research, with a qualitative approach, because the problems are holistic, complex and dynamic.The purpose of this study is to find out, examine, and analyze in depth the Strategy of Islamic Banks in Overcoming Financial Risk in the Covid-19 Pandemic Period.The results of the study concluded that the strategy of Islamic banks in overcoming financial risks during the COVID-19 pandemic was quite successful compared to conventional banks. Suggestions that can be given to improve the results of Islamic bank strategies in overcoming financial risks during the COVID-19 pandemic are 1) Improving the Information Technology System, 2) Developing more practical products, 3) Needing Human Resource Competence, 4) Harmonizing with regulators .Keywords: IT Expansion, Product Development, Human Resources Competence, Regulator